The Leu33/Pro Polymorphism (PIA1/PIA2) of the Glycoprotein IIIa (GPIIIa) Receptor Is Not Related to Myocardial Infarction in the ECTIM Study - Herrmann, Stefan-Martin; Poirier, Odette; Marques-Vidal, Pedro; Evans, Alun; Arveiler, Dominique; Luc, Gerald; Emmerich, Joseph; Cambien, François (Thrombosis and Haemostasis, 1997)
The GPIIb/IIIa receptor complex may contribute to acute coronary syndromes by mediating platelet aggregation. The Leu33/Pro polymorphism (PlAl/PlA2) of the GPIIIa has recently been shown to be associated with CHD in a small case-control study. We have investigated this polymorphism in a large multicenter study of patients with myocardial infarction and controls and found no difference in the distribution of allele and genotype frequencies between cases and controls.